Application and performance estimation of Mg/CO2 engine on Mars. (March 2022) - Li, Mengzhe; Hu, Chunbo; Wang, Zhiqin; Li, Yue; Hu, Jiaming; Hu, Xu; Li, Chao
Abstract: The production of return propellant through Martian in-situ resources has been proposed in the assumptions of Mars exploration missions. The Mg/CO2 scheme is one of these approaches in which powdered magnesium comes from the Earth as fuel and CO2 is collected on the surface of Mars as the oxidant. The propellant of Mg/CO2 engines has a good storage stability, has no chemical reactions in the in-situ resource utilization process, and contains a simple structure; thus, it is regarded as one of the technologically less complex choices for missions on Mars. However, the low specific impulse of Mg/CO2 engines requires evaluating their applications and performance. Three Mg/CO2 application scenarios (Ascent Vehicle, Hopper, and Two-stage Returnable Aircraft) are reviewed here, and two of them are estimated in detail from the established motion models. It is found that when a Mg/CO2 engine is used as an Ascent Vehicle, a two-stage rocket is more suitable. The propellant carried from Earth for Mg/CO2 engines could be reduced by 27.7% compared with the conventional storable UDMH/N2 O4 (specific impulse is 330 s) two-stage rocket. The saved propellant is largest when the total velocity pulse is approximately 3430 m/s. When Mg/CO2 engines are used as a jump vehicle "Hopper", the increased maximum thrust, engine working time, and total jump times decrease the marginal benefit, which means that these parameters cannot be too large. Based on the Ascent Vehicle and Hopper schemes, a Two-stage Returnable Aircraft is proposed for material and personnel circulation between different Mars bases. Highlights: Detailed motion models of Mars aircrafts with Mg/CO2 engine are firstly established. The advantages of Mg/CO2 engine as Mars Ascent vehicle are analyzed in detail. The influence of key parameters on the performance of Mars jump vehicle "Hopper" with Mg/CO2 engine is obtained. A new Mars two-stage returnable aircraft is conceived.